Optimization of Inventory Processes in University Laboratories Using Business Process Reengineering Method - Alam, Muhammad Bagus Nurul; Tirta, Jantera Sekar; Jamaludin, Fauzi (Sainteks: Jurnal Sain dan Teknik, 2025)
This study aims to optimize inventory management in university laboratories by redesigning the business process. The redesign is conducted using the Business Process Reengineering (BPR) approach. A lean-based analysis is applied to evaluate each inventory process by classifying them into value-adding, non-value-adding, or necessary but non-value-adding activities. The mapping of the initial inventory process and the development of improvement scenarios are carried out using Unified Modeling Language (UML). The redesigned inventory process is tested through simulation using iGrafx. Based on the simulation results, there is an improvement of 53% in the average processing time and 86% in the average waiting time. These improvements are achieved by merging compatible processes and implementing centralized storage.